Identification and Semi-Synthesis of 3-O-Protocatechuoylceanothic Acid, a Novel and Natural GPR120 Agonist † - Changjin Lim; Jung Gyu Park; Kyo Bin Kang; Young-Ger Suh (Molecules, 2019)
The identification and three step synthesis of 3-O-protocatechuoylceanothic acid, a novel and natural GPR120 agonist, is described. This ceanothane-type triterpenoid was identified from the components of Ziziphus jujuba roots and was found to be a new GPR120 agonist with a novel structure. We synthetically converted ceanothic acid, which does not have GPR120 agonist activity, into 3-O-protocatechuoylceanothic acid in three steps. In addition, we present the corrected NMR spectrum of 3-O-protocatechuoylceanothic acid based on our synthesis.